Pulsed VHE emission from the crab pulsar in the context of magnetocentrifugal particle acceleration - Osmanov, Zaza; Rieger, Frank M. (Monthly notices of the Royal Astronomical Society, 2016)
The Crab Pulsar has been recently detected at very high energies (VHE) with its pulsed VHE emission reaching up to 1.5 TeV. The VHE peaks appear synchronized with the peaks at GeV energies and show VHE spectra following hard power-law functions. These new findings have been interpreted as evidence for a γ-ray production that happens very close to the light cylinder. Motivated by these experimental results, we consider the efficiency of magnetocentrifugal particle acceleration in the magnetosphere of the Crab Pulsar, reexamining and extending results obtained in a previous work. It is shown that efficient magnetocentrifugal acceleration close to the light cylinder could provide the required electron Lorentz factors of 5 × 106 and that the resulting inverse Compton (IC) scattering off thermal photons might explain the enigmatic TeV emission of the pulsar. We estimate the corresponding VHE luminosity and provide a derivation of its spectral characteristics that appear remarkably close to the observational results to encourage further studies.